2020
DOI: 10.4314/rjmhs.v2i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health risks associated with medical waste management practices among health professionals working in three district hospitals in Rwanda

Abstract: BackgroundProper healthcare waste management is crucial to minimize the exposure of health professionals, patients, and the public in general, and to reduce the pollution of the environment in particular.In Rwanda, scientific documents on occupational health risks resulting from medical waste management practices among healthcare workers are currently rare. AimThis study aimed to explore occupational health risks associated with medical waste management practices among health professionals in the Rwandan conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In this study, we attempted to determine the status of occupational safety practices and associated factors among healthcare waste handlers in public hospitals situated in the South West Region of Ethiopia. In Ethiopia, despite highly infectious waste being generated in healthcare facilities, unsafe waste handling and management practices in public health facilities is one of the most typical problems experienced in the country [21,24,28]. In this study, it was revealed that the overall prevalence of good waste handling practices among healthcare waste handlers was 47.3%, which is low.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In this study, we attempted to determine the status of occupational safety practices and associated factors among healthcare waste handlers in public hospitals situated in the South West Region of Ethiopia. In Ethiopia, despite highly infectious waste being generated in healthcare facilities, unsafe waste handling and management practices in public health facilities is one of the most typical problems experienced in the country [21,24,28]. In this study, it was revealed that the overall prevalence of good waste handling practices among healthcare waste handlers was 47.3%, which is low.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, safety practices related to personal hygiene, medical waste handling, and the utilization of personal protective equipment, the availability of safety materials, and vaccination status were collected using a questionnaire with further crosschecking by observation. The questionnaire was developed after reviewing different studies [22][23][24][25][26][27], and modifications were also made to fit with our research objectives. The questionnaire contained both open-and closed-ended questions.…”
Section: Interviewer-administered Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…https://doi.org/10.53982/ajerd.2024.0701.02-j Raji et al Volume 7, Issue 1 https://doi.org/10.53982/ajerd Segregation of wastes is important as seen in a study where all the infectious wastes are not segregated; thus, leading to the wastes receiving the same treatment, thereby increasing the overall cost of managing the waste [44]. Improper medical waste separation increases the exposure of healthcare workers and waste handlers to infections, injuries, and other occupational risks [45]. In a study in Croatia, Kanisek et al [46] concluded based on their analysis that 60-80% of the sharp injuries in non-healthcare workers (cleaning staff) are due to improper mixing of sharp objects with infectious wastes.…”
Section: Solid Hcw Segregationmentioning
confidence: 99%